2020
DOI: 10.1371/journal.pone.0228551
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cancer survival by area-level socio-economic disadvantage: A population-based study using cancer registry data

Abstract: Despite overall improvements in cancer survival due to earlier diagnosis and better treatment, socioeconomically disadvantaged people have lower cancer survival than more advantaged people. We aimed to examine differences in cancer survival by area-level socioeconomic disadvantage in Victoria, Australia and assess whether these inequalities varied by year of diagnosis, age at diagnosis, time since diagnosis and sex. Cases diagnosed with a first primary cancer in 2001-2015 were identified using the Victorian Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
1
36
1
Order By: Relevance
“…Differences were detected, however, between patients living in locations with a health center and those living > 20 km from the nearest health center. Longer delay was not found to be related to distance from the hospital, which coincides with the findings of a study conducted in the United States [ 28 ], but is inconsistent with the results reported in other research [ 29 ]. Although provider delay showed no differences related to the distance from the hospital, differences were found as regards colonoscopy findings, where a higher percentage of lesions was found in patients that lived > 50 km from the hospital, while the percentage of advanced stage tumors was also slightly higher in this group.…”
Section: Discussioncontrasting
confidence: 96%
“…Differences were detected, however, between patients living in locations with a health center and those living > 20 km from the nearest health center. Longer delay was not found to be related to distance from the hospital, which coincides with the findings of a study conducted in the United States [ 28 ], but is inconsistent with the results reported in other research [ 29 ]. Although provider delay showed no differences related to the distance from the hospital, differences were found as regards colonoscopy findings, where a higher percentage of lesions was found in patients that lived > 50 km from the hospital, while the percentage of advanced stage tumors was also slightly higher in this group.…”
Section: Discussioncontrasting
confidence: 96%
“…However, similar disparities were not found in one UK study 22 . In Australia, socio‐economic status and region are reported to influence survival of people with any cancer and of those with various non‐haematological cancers, nationally, 23,24 and in Victoria 25,26 and New South Wales 10 . The Victorian study, which combined all leukaemia types, found that mortality was higher among patients from the most socially disadvantaged than for those from the least disadvantaged areas, 25 but found no difference in mortality for metropolitan and non‐metropolitan residents 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of sociodemographic factors have been associated with variation in outcomes for cancer survivors. Cancer survival is known to vary by socio-economic advantage/disadvantage [6][7][8][9][10][11] with this difference partly explained by variations in stage at diagnosis and treatment differences [6]. Recent evidence suggests that psychosocial factors including living alone, being unmarried and higher levels of depression can also negatively impact survival [12,13].…”
Section: Introductionmentioning
confidence: 99%